2013
DOI: 10.3748/wjg.v19.i36.5988
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture improves gut barrier dysfunction in prolonged hemorrhagic shock rats through vagus anti-inflammatory mechanism

Abstract: EA at ST36 attenuates the systemic inflammatory response, protects intestinal barrier integrity, improves organ function and survival rate after hemorrhagic shock via activating the cholinergic anti-inflammatory mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 38 publications
(47 reference statements)
0
41
0
1
Order By: Relevance
“…Data indicate that either auricular electrostimulation[111], acupuncture[112, 113] or electroacupuncture[114] on ST36 can attenuate serum concentrations of inflammatory cytokines TNF, IL-1β and IL-6, as well as improve kidney and lung injury in septic rodents. These mechanisms are not specific to sepsis, and electroacupuncture on ST36 can also prevent intestinal injury in ischemic and hemorrhagic rodents [115]. Mechanistically, these effects were reported to occur via the vagus nerve as they were prevented by surgical vagotomy [2, 116].…”
Section: Neuro-immunomodulation and Functional Organization Of The Nementioning
confidence: 99%
“…Data indicate that either auricular electrostimulation[111], acupuncture[112, 113] or electroacupuncture[114] on ST36 can attenuate serum concentrations of inflammatory cytokines TNF, IL-1β and IL-6, as well as improve kidney and lung injury in septic rodents. These mechanisms are not specific to sepsis, and electroacupuncture on ST36 can also prevent intestinal injury in ischemic and hemorrhagic rodents [115]. Mechanistically, these effects were reported to occur via the vagus nerve as they were prevented by surgical vagotomy [2, 116].…”
Section: Neuro-immunomodulation and Functional Organization Of The Nementioning
confidence: 99%
“…The authors concluded that EA combined with delayed fluid replacement was protective against hepatic ischemia in rats following HS. These results alongside the results from their later study (Du et al 2013), which includes data from a control group that underwent vagotomy before EA, indicate that EA at ST36, even though not directly stimulating the vagus nerve, does act, at least partially, through the vagal signaling pathway.…”
Section: Electroacupuncturementioning
confidence: 55%
“…The effects of EA at ST36 to decrease gut barrier dysfunction have also been investigated (Du et al 2013). In a study by Du et al, a wider range of biological markers, including MAP, interleukin-6, interleukin-10, TNFor-α organ parameters, gut injury score, gut permeability to 4 kDa FITC-dextran, and expression and distribution of tight junction protein ZO-1, as well as simple survival counts, were investigated.…”
Section: Electroacupuncturementioning
confidence: 99%
“…As we all know, intravenous fluid resuscitation is usually difficult to administer in some environments. In recent years, we have been working on alternative methods to solve the complications caused by delayed fluid resuscitation and we have proved that EA at ST36 can significantly protect the intestinal barrier integrity and improve organ function and survival rate after fatal hemorrhagic shock in rats [7, 8]. Recent studies showed that electrical stimulation of the vagus nerve could protect alleviation of inflammatory injuries and remote organs of animals following burn injuries by activation of the cholinergic anti-inflammatory pathway [22].…”
Section: Discussionmentioning
confidence: 99%
“…Research [5, 6] indicates that EA at ST36 can promote periphery nerve endings producing acetylcholine, enhancing the activity of acetylcholine, and activating the cholinergic anti-inflammatory pathway. It has positive therapeutic implications on a series of inflammatory reactions that occur during shock, protecting the functions of organs of the body after shock [7]. One of our previous studies [8] showed that the ST36 acupuncture point improved rehydration and rats' blood pressure levels and decreased the survival rate of rats in hemorrhagic shock.…”
Section: Introductionmentioning
confidence: 99%